Hydrological and Radiological Studies of Water Resources by Using Radon in Hashimiya Area- Middle of Iraq. - Ali , Kamal K.; Al Maimuri, Najah M. L.; Hasson, Muhsen K. (Iraqi Journal of Science, 2022)
Radon concentrations are measured for water samples collected from twenty wells which were drilled in Hashimiya area in addition to twelve samples of surface water using Alpha Gaurd. 140 samples, 7 for each well, were collected represent wet season in continuous pumping and 20 samples, one for each well, were collected represent dry season. Concentration of radon in groundwater is many times of its concentration in surface water. The minimum concentration in groundwater is about (7) Bq/L and (5) Bq/L while the maximum concentration is about (31) Bq/L and (19) Bq/L in wet season and dry season respectively. The range of radon concentrations in river water is between (1.06) Bq/L and (1.21) Bq/L. This study has indicated that there is a flow from river water towards shallow groundwater in the closed wells especially in wet period. This is concluded by occurring a dilution of groundwater with that of the river water of low concentration of radon. On the other hand, there is a flow of deep groundwater with elevated concentration of radon to the shallow groundwater which caused to an increase of the concentration of radon in these wells. From the radiological point of view, due to consuming their water, all the wells offer annual effective dose greater than 0.1 mSv which is the recommended value by UNSCEAR. So, these considered as radon contaminated wells and need for remediation before their water is used or consumed.